Musiqiy asarlarda matn talaffuzi ustida ishlash - Diyora Yuldasheva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the correct use of speech and expressions, in turn, are exercises to achieve correct pronunciation through some pedagogical and methodological techniques for speech techniques. Working on the text of consonants and vowels through the basics of vocal technique several issues of timbre, dynamics and sound are taught and covered.